Analysing Relationally Entangled Sustainable Learning Environments for Employability of Accounting Teacher Education Graduates in Unequal Post COVID - 19 Contexts - Makeresemese, Mahlomaholo Rosy (Research in Social Sciences and Technology- OpenED Network, 2025)
South Africa is still burdened by its history of colonisation and apartheid, manifesting through a high burden of disease due to rampant poverty, which is a function of unprecedentedly low rates of employment, estimated to be around 37 % among the 18- to 34-year-old Black African youth. The intersectionality of inequalities regarding race, rural versus urban divide, gender binaries, and socio-economic status, among others, seems to be a significant determinant of such. To remedy the problem, attempts have been made to increase the levels of education among the youth. Unfortunately, even the Black African graduates also seem to swell the ranks of the unemployed. In this paper, through qualitative approaches of participatory action research, we exemplify how transforming the Accounting Teacher Education Programme (ATEP), guided by equally multi-perspectival and multilayered lenses of relationality and entanglement learned from COVID-19’s experiences, enabled the study to promote holistic approaches towards achieving positive developmental outcomes and increased possibilities of employment.